Geotechnical Challenges of Pile Driving in a Marginally Stable Slope Terminal 46 Apron Upgrade, Port Of Seattle, WA (18615664-0169-4e91-aa2b-8ec5994bb0a0) - Monique Nykamp (Deep Foundations Institute, 2007)
"INTRODUCTIONTerminal 46 is located just south of downtown Seattle, and is one of the Port of Seattle’s busiest container terminals. The Terminal 46 Redevelopment Project was undertaken to replace the existing 15-m-wide (50 ft) cranes along the apron with 30-m-wide (100 ft) cranes, which can unload larger, post- Panamax ships. The project included upgrading the existing waterside crane rail with new piles and constructing a new land-side rail behind the sheetpile bulkhead. The new piles had to be installed adjacent to the existing apron without causing damage, which was a signifi cant geotechnical challenge due to the soft soil conditions at the site. An instrumentation program performed during the test pile program evaluated this challenge and allowed for the development of specifi c production pile installation procedures that had the least possible effect on construction costs and schedule. SITE HISTORYThe site lies along the west side of Elliott Bay, north of the mouth of the Duwamish Waterway. Prior to development, this area was part of the tide fl ats where the Duwamish River drained into Elliott Bay. Prior to 1970, there were several existing timber piers and structures in the area. In the 1970s, the Port of Seattle constructed a 900-m-long (3,000 ft), 30- m-wide (100 ft) apron to support fi ve, 15-m-wide (50 ft) container cranes. The contained backland area was then fi lled with dredged spoils (sand and silt with organics) and the upper 5 to 20 m (16 to 65 ft) backfi lled with sand and gravel.The existing apron was constructed using 0.4 m (16 in) octagonal prestressed concrete piles to support the precast concrete deck and crane rails. The pile-supported bents were spaced at 6.1 m (20 ft), center-to-center, along the longitudinal direction. Pile lengths typically varied from about 20 to 40 m (65 to 130 ft) with 15 to 26 m penetration below mudline (50 to 85 ft penetration). The slope below the apron was constructed at about 1.75 horizontal to 1 vertical to allow for suffi cient water depth for cargo ships. In most areas, a riprap buttress was placed at the toe of the slope. A typical cross section of the apron is shown on Figure 2.Several stability, settlement and pile driving issues arose during the original construction of T-46 (Pita, 1983). Reportedly, movement of the submarine slope occurred during pile driving, resulting in settlement behind the bulkhead. Pile driving reportedly caused settlement of adjacent piles. In addition, some piles were “running” (dropping quickly under one hammer blow) during installation."